Peripheral functional organisation of vagally evoked gastric motor responses in the ferret. Issue 10 (October 1980) - Andrews, P L; Lawes, I N; Bower, A J
Abstract : The aims of the present study were to determine the relative amplitudes of intragastric motor responses evoked by different vagal branches and to establish whether the effects of acute or chronic vagotomy could be predicted from these data. Intragastric pressure responses to electrical stimulation of the vagus were measured in urethane-anaesthetised ferrets and acute or chronic vagotomies were performed. The results show that the left and right cervical vagi were equipotential and fully overlaped each other. Their contributions to the dorsal trunk were equipotential and fully overlapping and so were their contributions to the ventral trunk. The dorsal trunk was more effective than the ventral trunk and there was total functional overlap between these two trunks. Vagal evoked gastric motor responses of the ferret are apparently organised in a different way from vagally induced acid secretion or hormone release in the cat. Acute removal of a trunk led to a reduction in evoked responses that was not linear function of the effect of stimulation of that trunk. In contrast, chronic removal caused a relative increase in evoked responses that ws inversely related to the decrease caused by acute removal. The implications of total functional overlap and neuromuscular reorganisation after chronic vagotomy are discussed.